A General Organocatalytic System for Enantioselective Radical Conjugate Additions to Enals - Le Saux, Emilien (Angew Chem Int Ed Engl, 2021)
Herein, we report a general iminium ion‐based catalytic method for the enantioselective conjugate addition of carbon‐centered radicals to aliphatic and aromatic enals. The process uses an organic photoredox catalyst, which absorbs blue light to generate radicals from stable precursors, in combination with a chiral amine catalyst, which secures a consistently high level of stereoselectivity. The generality of this catalytic platform is demonstrated by the stereoselective interception of a wide variety of radicals, including non‐stabilized primary ones which are generally difficult to engage in asymmetric processes. The system also served to develop organocatalytic cascade reactions that combine an iminium‐ion‐based radical trap with an enamine‐mediated step, affording stereochemically dense chiral products in one‐step.